Etika Islam sebagai Perspektif Hukum Kontemporer - Barri, Hammadul; Naseh, Ahmad Muhammad (UAS PRESS, 2025)
This jurnal examines the relevance of Islamic ethics as an alternative perspective in contemporary law, which is currently facing moral crises, degradation of human values, and global challenges such as human rights, bioethics, economic injustice, and ecological crises. This research employs a qualitative approach through library studies, analyzing classical sources such as al-Ghazālī and al-Syāṭibī, as well as contemporary thought from scholars including M. Hashim Kamali, Abdulaziz Sachedina, M. Umer Chapra, and Seyyed Hossein Nasr. The findings indicate that the principles of maqāṣid al-sharī‘ah—covering the protection of religion, life, intellect, lineage, and property—are highly relevant in addressing the problems of modern law. Regarding human rights, Islamic ethics emphasizes the balance between rights and responsibilities through the concept of karāmah insāniyyah (human dignity). In bioethics, the principles of lā ḍarar wa lā ḍirār and ḥifẓ al-nafs provide moral guidance in responding to modern biotechnology. In the economic sphere, Islamic ethics offers distributive justice through instruments such as zakat and the prohibition of usury, serving as a corrective to the weaknesses of capitalism and socialism. Meanwhile, in environmental law, the paradigms of khalīfah (stewardship) and al-mīzān (balance) emphasize humanity’s responsibility to preserve the sustainability of nature as a divine trust. The article concludes that Islamic ethics can serve as a constructive partner to positive law through an interdisciplinary approach and the reinterpretation of maqāṣid in accordance with contemporary contexts. The study recommends the need for dialogue between positive law and Islamic ethical values to create a legal system that is more humane, just, and sustainable.